Optimizing gamma irradiation for mutation breeding in seedless barberry (Berberis vulgaris L.): Establishing LD50 and GR50 thresholds - Mehri Asadi Zargh Abad; Gholamreza Rabiei; Ali Akbar Ghasemi-Soloklui; Mojtaba Kordrostami; Mohammad Rabiei (PLoS ONE, 2025)
Native to Iran, seedless barberry ( Berberis vulgaris L.) is a nutritionally and economically important crop prized for its therapeutic uses and food industry applications. Nevertheless, the vegetative propagation of the plant and lack of seeds limit conventional breeding techniques, therefore reducing genetic variation and impeding cultivars improvement. This work sought to maximize gamma radiation dosages to cause mutations in seedless barberry hence increasing genetic variability for breeding projects. Hardwood cuttings were subjected to gamma radiation dosages of 0 (control), 10, 20, 30, 40, 50, 60, 70, 80, 90, and 100 Gy using a Cobalt-60 source. Under both in vitro and in vivo settings, the impacts on survival rates, leaf and shoot development, and morphometric features were assessed. Results revealed that rising radiation doses significantly reduced survival rates and growth metrics. The LD 50 (Lethal dose) was determined to be roughly 19 Gy for the in vivo and 13.6 Gy for the in vitro. Gamma irradiation negatively influenced plant growth according to values for leaf length, leaf width, fresh weight, and dry weight growth reduction (GR 50 ). Optimal dosages for causing mutations, while preserving survival, were found to be 15 Gy for the in vivo and 10 Gy for the in vitro.